Types of allergen affecting asthmatic children - M. P. Damanik; A. Samik Wahab; Ediyono Ediyono; Ismangoen Ismangoen (Paediatrica Indonesiana, 1984)
An intracutane tuberculin test with several types of allergens was conducted on 110 asthmatic children under the age of 14 years at the Subsection of Allergic diseases and Immunology of the Internal Diseases Section, in cooperation with the Department of Child Health, Gajah Mada University, Pugemn Hospital, in Yogyakarta. The number of children found to be sensitive to house dust, human dander, grass pollen, fungus, collection of animal danders, "mite" (Pteronysinus pterygoideus), and bacteria vaccine were 82 (75,5%), 80 (72. 7%), 0 (0%), 3 (2. 7%), 1 (0,9%), 23 (20.9%), and 20 {18.1%), respectively. It was also found that four ( 3.6%) of the children did not develop any reaction to all allergen types. It was further concluded that the numbers of children being allergic to just one type of allergen were as follows : house dust 2 (1.8%); human dander 0 (0%), hence all patients allergic to the human dander were also allergic to house dust; fungus 1 (0.9%); collection of animal danders 1 (0.9%); "mite" 2 (1.8%); bacteria 19 (17.3%). The highest incidence of reaction to more than one allergen were to house dust+human dunders: 80 (72. 7%); to house dust+ "mite": 21 (21.91%); and to house dust+human dander +"mite": 17 ( 15.5%).